Targeting RNA-Mediated Toxicity in C9orf72 ALS and/or FTD by RNAi-Based Gene Therapy - Raygene Martier; Jolanda M. Liefhebber; Ana García-Osta; Jana Miniarikova; Mar Cuadrado-Tejedor; Maria Espelosin; Susana Ursua; Harald Petry; Sander J. van Deventer; Melvin M. Evers; Pavlina Konstantinova (Elsevier, 2019)
A hexanucleotide GGGGCC expansion in intron 1 of chromosome 9 open reading frame 72 (C9orf72) gene is the most frequent cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). The corresponding repeat-containing sense and antisense transcripts cause a gain of toxicity through the accumulation of RNA foci in the nucleus and deposition of dipeptide-repeat (DPR) proteins in the cytoplasm of the affected cells. We have previously reported on the potential of engineered artificial anti-C9orf72-targeting miRNAs (miC) targeting C9orf72 to reduce the gain of toxicity caused by the repeat-containing transcripts. In the current study, we tested the silencing efficacy of adeno-associated virus (AAV)5-miC in human-derived induced pluripotent stem cell (iPSC) neurons and in an ALS mouse model. We demonstrated that AAV5-miC transduces different types of neuronal cells and can reduce the accumulation of repeat-containing C9orf72 transcripts. Additionally, we demonstrated silencing of C9orf72 in both the nucleus and cytoplasm, which has an added value for the treatment of ALS and/or FTD patients. A proof of concept in an ALS mouse model demonstrated the significant reduction in repeat-containing C9orf72 transcripts and RNA foci after treatment. Taken together, these findings support the feasibility of a gene therapy for ALS and FTD based on the reduction in toxicity caused by the repeat-containing C9orf72 transcripts. Keywords: C9orf72, ALS, FTD, miRNA, gene therapy, AAV